Enhanced Antioxidant and Digestive Enzyme Inhibitory Activities of Pacific White Shrimp Shell Protein Hydrolysates via Conjugation with Polyphenol: Characterization and Application in Surimi Gel - Akanksha R. Gautam; Soottawat Benjakul; Deepak Kadam; Brijesh Tiwari; Avtar Singh (Foods)
Pacific white shrimp shell protein hydrolysates (SSPHs) produced using alcalase (UAH) and papain (UPH), and polyphenols (PPNs) conjugates were prepared using variable concentrations (0.5–3% w/v) of different polyphenols (EGCG, catechin, and gallic acid). When 2% (v/v) of a redox pair was used for conjugation, 0.5% (w/v) of PPNs resulted in the highest conjugation efficiency (CE), regardless of the polyphenol types. However, CE decreased further with increasing levels of PPNs (p < 0.05). SSPHs at 2% retained the highest CE when combined with the selected PPN and redox pair concentrations (p < 0.05). FTIR and 1H-NMR analysis confirmed the successful conjugation of PPNs with the SSPHs. Among all the conjugates, EGCG conjugated with UAH (A–E) or UPH (P–E) exhibited the highest DPPH/ABTS radical scavenging, and metal chelating activities, respectively. The highest FRAP activity was noticed for A–E conjugate followed by UAH-catechin (A–C) and UPH-catechin (P–C) conjugates. The A–C sample (6 mg/mL) demonstrated the strongest inhibition efficiency against α-amylase, α-glucosidase, and pancreatic lipase (89.29, 81.23, and 80.69%, respectively) than other conjugates (p < 0.05). When A–C conjugate was added into surimi gels prepared from Indian mackerel (IM) and threadfin bream (TH) mince at various levels (2–6%; w/w), gel strength, and water holding capacity was increased in a dose-dependent manner, regardless of surimi type. However, whiteness decreased with increasing A–C levels. After the in vitro digestion of surimi gels, antioxidant and enzyme inhibitory activities were also increased as compared to the digest prepared from control surimi gels (added without A–C conjugate). Thus, waste from the shrimp industry in conjugation with plant polyphenols could be utilized to produce antioxidant and antidiabetic or anti-obesity agents, which could be explored as a promising additive in functional foods and nutraceuticals.